PARENTAL SUPPORT DALAM KONSEP PSIKOLOGI PERKEMBANGAN PIAGET PADA ANAK USIA SEKOLAH DASAR - A'yun, Mayada Izzatul; Sa’diyah, Elok Halimatus (PREMIERE : Journal of Islamic Elementary Education, 2024)
Parental support plays a crucial role in facilitating children's development. However, some parents do not support their children's cognitive development enough, which impacts their learning outcomes. This study aims to examine how parental support fits with Piaget's developmental psychology theory as it relates to children in elementary school. This research uses a qualitative research methodology with literature study techniques using content analysis. Based on research findings, (1) Piaget's theory about the cognitive development of elementary school-aged children. This process requires the involvement of parents and teachers, both of whom need to realize that children learn in different ways, at different times, and with different levels of interest. -different. This must be paid attention to in order to achieve a perfect cycle. (2) Parental support plays an important role in fostering learning motivation in elementary school students, including emotional, appreciative, instrumental and informative aspects. (3) So that children can reach their maximum cognitive potential, forms of parental support should be adapted to Piaget's 4 stages of development theory.